Public Expenditure Management in Francophone Africa : A Cross-Country Analysis - Moussa, Yaya (IMF Working Papers; Working Paper, 2004)
There are strong similarities between the French and French-inspired African PEM systems in terms of the legal setting, rules, and procedures. However, there are differences in practice, particularly in accounting and reporting, audit, and external control. Among the African countries themselves, there are many common features but also marked differences in audit and external control.